(untitled) (Kairaranga, 2023)
Kia ora koutou Ko Hikurangi te maunga Ko Waiapu te awa Ko Ngāti Porou te iwi Ko Rongohaere te marae Ko Rebekah Corlett toku ingoa I’m a mum to Sophia who is fourteen. She was diagnosed as autistic at age 2 1/2; she is non- speaking and uses Augmentative and Alternative Communication (AAC) to communicate which for her is an iPad with a communication app on it. She uses a mixture of a few spoken words, AAC, a few NZSL signs and lots of gestures. That’s how she makes herself known. We live on the Kapiti Coast which is about an hour north of Wellington. I live with my husband Jason and also our son Ryan who is eleven. Sophia is ORS funded, and she has moved in the last couple of years from a specialist primary school to a mainstream high school, which has been a massive undertaking and mostly successful. I write a blog Reasonable Accommodations with Rebekah which explains what those experiences and education are like, and gives a voice to whānau who are supporting and keeping their child or young person engaged in the education system.